"Music in Mind" and Manchester Camerata: an exploratory qualitative evaluation of engagement in one care home in Northwest England. (13th March 2017) - Campbell, Sarah; Ponsillo, Nick; Budd, Paul; Keady, John
Abstract : Purpose: The purpose of this paper is to consider the work conducted by Manchester Camerata (an internationally renowned and world-class chamber orchestra) programme for people with dementia in one care home in the north west of England. The study aim was to undertake an exploratory qualitative evaluation of experiences of those taking part in its ten week "Music in Mind" programme, namely care home staff, Manchester Camerata musicians/organisational staff, care home activity workers, the assigned music therapist and visiting family carers. Design/methodology/approach: During July-September 2014 a sample of 11 participants was recruited and a total of 19 interviews conducted over ten weeks. All respondents were offered the opportunity to be interviewed more than once. Interview data were supplemented by information gathered at two musicians de-brief sessions and from two activity workers' diaries. All data was organised using NVivo 10 and thematic analysis applied to the whole data set. People with dementia could not be included in the sample owing to the time limitations on starting and completing the evaluation. Findings: This analytical process generated three overarching themes: Making it Happen, which referred to the contextual, structural and organisational considerations necessary for setting up the engagement programme; Orchestrating Person-centred Care, which addressed the importance of building relationships through person to person communication; Making Musical Connections, which identified the sensory and embodied qualities of live music and the need to capture in-the-moment experiences. Originality/value: Whilst each of these theme headings has slightly different meanings and applications to each of the participating stakeholders, the evaluation highlights the potential power of improvised music making to equalise and harmonise the group dynamics by co-creating "in-the-moment" experiences.